European gender equality under and after State Socialism: legal treatment of prostitution in the Czech Republic - Havelková, B (2010)
The thesis looks at the legal responses to prostitution in Czechoslovakia and the Czech Republic under State Socialism and in Transition, and the understanding of gender equality therein. It argues that both, the legal regimes and the understandings of prostitution, varied between these periods. Under State Socialism, professional prostitutes were criminally liable under provisions on parasitism. In Transition, the ‘boom’ of prostitution after 1989 lead to the adoption of containment provisions, the violation of which results in fines for prostitutes. While being repressive toward prostitute as a work-shirker, the Socialist State, inspired by Marxist ideology, had aspirations to eliminate prostitution, which it saw as exploitation of women. Policy influencing actors in Transition, on the other hand, have become resigned to its existence. Prostitution has been seen as pathological but inevitable. As prostitutes have been mostly considered agents making free choice, they have been treated as legitimate objects of containment, state regulation and control. Gender equality, it is argued, was insufficiently considered during both periods. Because feminists (the sex-work and the sexual domination positions) fundamentally disagree about the best legislative regime, the thesis chose to work with the standard of ‘well-being of the prostitute’. At least, this requires for prostitutes not to be treated worse than procurers or clients, for example with regards to administrative, health or criminal obligations and liability. The thesis argues that State Socialism as well as Transition failed this minimal test – both regimes are marked by an absence of feminist analysis of the phenomenon of prostitution and a legal conceptualization of it as a gender equality issue.